Effect of build direction on tension–tension low cycle fatigue behavior of polyamide 12 parts printed by Multi Jet fusion - Chen, Kaijuan (2023)
The effects of build direction on the tensile properties, tension–tension low cycle fatigue behavior, and failure mechanism of polyamide 12 parts fabricated by Multi Jet Fusion have been investigated by addressing the roles of formed voids, sintering interfaces, and geometrical imperfections. Results indicate that the Young's modulus of bulk material with vertical build direction is higher than that of bulk material with horizontal build direction due to the carbon black enhanced sintering interfaces. The tensile strength of the printed bulk material with horizontal and vertical build directions is comparable. It is found that the anisotropic tension–tension low cycle fatigue behavior for the bulk material is significant, while that for the re-entrant lattice structure is weak. The anisotropic fatigue strength of bulk material is derived from the anisotropic distribution of internal voids and sintering interfaces. The fatigue behavior of the re-entrant lattice structure is determined by the geometrical imperfections. The coalescence of the large voids or clusters of voids contributes to the crack initiation and propagation processes that lead to the failure of the bulk material. While the failure of re-entrant lattice structure is mainly determined by the intersection of strut junction rather than the void defect. This result provides the fatigue data that can be used for the structural design with Multi Jet Fusion polyamide 12 as well as reveals the effects of voids, sintering interfaces, and geometrical imperfections on the fatigue behavior of the printed parts.